Análisis de calidad del servicio en la empresa Roma Pizzería, del cantón de Loja, provincia de Loja - López Cuenca, Karen Krupskaya (2019)
The present research project exposes an analisis about the servicie quality of the "ROMA PIZZERIA" from Loja City. This study arises from the need to improve the service quality offered to tourists or consumers. The reasearch has the following general objetive “To analyze the quelite service that “Roma Pizzeria” local company is offering to the costumers from Loja City and Province.The research contains specific objectives for the fulfillment of it which are: “Identify the current situation of "ROMA PIZZERIA" company, from Loja City”, the other objective is “Ton know the kind of service that "ROMA PIZZERIA" local company offered to the consumers, through the SERVQUAL method and propose strategies for the improvement the services quality in the restaurant". For development the first specific objective, two diagnostic sheets were needed to apply, the first one, was a useful sheet to collect general information about the enterprise. The second one was Tourism Ministry sheet, it contains; general data, the enterprise regulations, the infrastructure requirements based on Ecuador Tourism establishment guidelines and regulatory institutions such as: Tourism Ministry, the Employment Ministry, CONADIS, ARCSA, ARCHA, Loja Municipality; then to gather more information, two interviews were prepared, one focused on the restaurant employees and the other one with the manager, with the aim to get more specific information. Finally, FODA Matrix was carried out, it was focused on the internal restaurant part, in order to know, the Weaknesses and Strengths of this food establishment. The second objective implementation was based on the SERVQUAL method that allows measuring the expectations and perceptions that customers have about the service admitted within the five dimensions (tangible elements, reliability, sensitivity, empathy and security), this method is used for Preparation of the surveys that are going to apply. After that information from the surveys was analyzed, the second part of the FODA Matrix focused on the external part was elaborated; it is based on the Opportunities and Hazards in order to compare them and carry out the strategic FODA Matrix that will contribute to the improvement strategies for the company. Finally, for carring out the third objective, the strategies that help the restaurant to improve its service quality were proposed, where a table was prepared for each strategy, explaining in detail what the strategy: characteristics, policies, indicators, tentative goals and prices consist. According to the diagnostic card results, the restaurant meet with the most requirements, nevertheless, it still has a deficiency inside of the CONADIS regulations, the company does not have a braille system to provide necessary facilities for the care of people with disabilities As for the results of the survey showed that certain number of clients are not 100% satisfied with the services received due to their deficiencies such as: the staff does not comply with the protocol to serve the product on the table, restaurant opening and attention are not adequate, does not offer information about the rules in the restaurant. In conclusion, once the main weaknesses have been known some suggestions were exposed to the company directives for instance: training the human resources and of this way create a competitive advantage within the company. In addition is recommended to implement the suggested strategies because it is a great way to improve the quality service to the client.